2023
DOI: 10.1097/ms9.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical site infection among women following cesarean delivery in eastern Ethiopia: a prospective cohort study

Abstract: Background: Despite the availability of prophylactic antibiotics prior to skin incisions, surgical site infection (SSI) following cesarean section (CS) remains an unresolved health issue. As a result, this study aimed to assess the incidence and predictors of SSI after a CS. Methods: The authors conducted a prospective cohort study in eastern Ethiopia. The women were serially enrolled until the desired sample size was reached. A structured questionnaire was used to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Six studies ( 35 , 37 , 38 , 41 , 49 , 52 , 54 ) were included to determine the relationship between emergency cesarean sections and surgical site infections. Except for the one study ( 35 ) that found a significant association, the remaining five studies ( 37 , 38 , 41 , 49 , 52 , 54 ) did not find a significant association.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies ( 35 , 37 , 38 , 41 , 49 , 52 , 54 ) were included to determine the relationship between emergency cesarean sections and surgical site infections. Except for the one study ( 35 ) that found a significant association, the remaining five studies ( 37 , 38 , 41 , 49 , 52 , 54 ) did not find a significant association.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies ( 35 , 37 , 38 , 41 , 49 , 52 , 54 ) were included to determine the relationship between emergency cesarean sections and surgical site infections. Except for the one study ( 35 ) that found a significant association, the remaining five studies ( 37 , 38 , 41 , 49 , 52 , 54 ) did not find a significant association. This meta-analysis revealed that no relationship existed between emergency cesarean section and surgical site infection (AOR = 1.09.95% CI: 0.95–1.24), with no heterogeneity (I 2 = 0, p = 0.721; Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations